KEBENCIAN DAN AMARAH TOKOH EKSIL DALAM CERPEN TANAH AIR DAN ASMARA DAN KEMATIAN DI PERBATASAN TIGA NEGARA KARYA MARTIN ALEIDA - Syahwan Alfianto Amir; Inriati Lewa; M. Syafri Badaruddin (Universitas Hasanuddin, 2020)
This research aims to elaborate the manifestations of hate and anger of the exile characters in the short stories of Tanah Air and Asmara dan Kematian di Perbatasan Tiga Negara by Martin Aleida. This research used qualitative analysis by using descriptive method. The technique of data collections used library research or content analysis. The result of the study shows that hate and anger of the exile characters in both short stories by Martin Aleida, according to the psychology existential by May divided into two categories. These categories come to animate the story that starring by the characters who deliberately labelled as an exile. There are two types of hate and anger in the exile characters is hate and anger of the regime and hate and anger of their self. In the short story of Tanah Air, the two categories come to affirm the occasion of a phenomenon and in the short story Asmara dan Kematian di Perbatasan Tiga Negara, only one category that begins to build the occasion of the short story. The result that the exile characters reveal their existence by showing hate and anger to the regime.